Cover Picture: Pleiotropic Role of Recombinant Silaffin‐Like Cationic Polypeptide P5S3: Peptide‐Induced Silicic Acid Stabilization, Silica Formation and Inhibition of Silica Dissolution (ChemistrySelect 1/2017). Issue 1 (9th December 2016) - Spinthaki, Argyro; Zerfaß, Christian; Paulsen, Harald; Hobe, Stephan; Demadis, Konstantinos D.
Abstract : The cover picture shows a designed recombinant peptide which exerts triple control over silica chemistry: it delays condensation of slightly supersaturated silicic acid solutions, enhances precipitation of colloidal silica at higher silicic acid concentration and decelerates hydrolysis of colloidal silica at non‐saturated conditions. Peptide and silicic acid/silica interactions take place via ionic bonds between protonated nitrogens (in blue) with anionic silicate (‐SiO ‐ ), and H‐bonds between backbone oxygens (in red) with silanols (‐SiOH). More information can be found in the Full Paper by Spinthaki et al. (DOI:10.1002/slct.201601086 ). The artwork was created by Dr. Christian Zerfaß, with the programs GIMP, ACD/ChemSketch, UCSF Chimera and Power Point.